X-ray mineralogy and geochemical studies of sediments: Leg 125 Sites 781 through 784 and 7861 - Heling, Dietrich; Schwarz, Alexander; Garbe-Schönberg, Carl-Dieter (ODP proceedings. Scientific results, 1992)
The mineral composition of clay (<2 µm)- and silt (<63 µm)-fractions from sediments sampled at Sites 781 through 784 and 786 from the Mariana and Izu-Bonin forearcs (ODP Leg 125), were investigated by X-ray diffraction analysis. The concentrations of major and trace elements of selected samples were determined by X-ray fluorescence analyses and the rare earth elements by ICP mass spectrometry.
Elektronische Reproduktion der Druck-Ausgabe 4. Dezember 2006
Gesehen am 20.03.2023